Different Types of Field-Effect Transistors Theory and Applications - Pejovic, Momcilo M.; Pejovic, Milic M. (IntechOpen, 2017)
In 1959, Atalla and Kahng at Bell Labs produced the first successful field-effect transistor (FET), which had been long anticipated by other researchers by overcoming the "surface states" that blocked electric fields from penetrating into the semiconductor material. Very quickly, they became the fundamental basis of digital electronic circuits. Up to this point, there are more than 20 different types of field-effect transistors that are incorporated in various applications found in everyday's life. Based on this fact, this book was designed to overview some of the concepts regarding FETs that are currently used as well as some concepts that are still being developed.